2020
DOI: 10.2298/abs200107012c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kinetin on biological parameters and hemocytes of Achroia grisella (Lepidoptera: Pyralidae)

Abstract: The effects of the cytokinin hormone kinetin on the life history traits and hemocytes of the smaller wax moth Achroia grisella F. (Lepidoptera: Pyralidae) were examined in order to better understand the physiological impacts of plant growth regulators on insects. Based on the obtained results, it was found that kinetin did not lead to significant changes in larval mortality, development time, morphological disorders and egg fertility. Female and male longevity were almost unchanged when early instars were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Also, the application of GA3 had no influence on the pupal duration of S. oblique (Gupta et al, 2009).In a recent study, the foliar treatments of maize with GA3 and JA against S. frugiperda resulted in no significant effect on larval duration (Nagaratna et al, 2021). Çelik and Sak (2021) investigated the effect of kinetin against A. grisella and found no significant change in thedevelopment duration.…”
Section: Prolonged Developmental Durations and Regressed Developmental Ratementioning
confidence: 98%
See 1 more Smart Citation
“…Also, the application of GA3 had no influence on the pupal duration of S. oblique (Gupta et al, 2009).In a recent study, the foliar treatments of maize with GA3 and JA against S. frugiperda resulted in no significant effect on larval duration (Nagaratna et al, 2021). Çelik and Sak (2021) investigated the effect of kinetin against A. grisella and found no significant change in thedevelopment duration.…”
Section: Prolonged Developmental Durations and Regressed Developmental Ratementioning
confidence: 98%
“…IAA failed to display chronic toxicity on the developed pupae or emerged adults except for its 1.00ppm at which the emerged adults completely died. Also, the present results may be in corroboration with some reported results of different PGRs' toxicities against various insects, such as miraculan and milstim (Harikesh and Blattacharya, 2001) and Gibberellic acid (GA3) (Shiwani and Karnatak, 2012) against the tobacco cutworm Spodoptera litura; GA3 against the Egyptian cotton leafworm Spodoptera littoralis larvae and the migratory locust Locusta migratoria nymphs (Abdellaoui et al, 2009(Abdellaoui et al, , 2013; Coumarins (Cns) against the melon fly Bactrocera cucurbitae (Kaur and Rup, 2003) and the fall armyworm Spodoptera frugiperda (Vera et al, 2006); GA3 and jasmonic acid (JA) against S. frugiperda (Nagaratna et al, 2021); Siapton against the jute hairy caterpillar Spilarctia oblique (Gupta et al, 2009); and kinetin against the lesser wax moth Achroia grisella (Çelik and Sak, 2021).…”
Section: Affected Survival Of G Mellonella Byindole-3-acetic Acid (Iaa)mentioning
confidence: 99%
“…The results of some studies revealed that different botanicals cause much variation in the proportions of hemocyte populations in various insects (Er et al, 2017;Shaurub and Sabbour, 2017) In addition, the cytopathological effects of plant extracts and products on the hemocytes have been reported in a few insect species (Sharma et al, 2001(Sharma et al, , 2003(Sharma et al, , 2008. Also, the antimitotic effects of some botanicals have been demonstrated in the cell lines of various insect species (Salehzadeh et al, 2003;Huang et al, 2011;Er and Keskin, 2016;Çelik et al, 2017). Moreover, the influence of botanicals on insect heart activity was recorded in few studies (Marciniak et al, 2010;Ntalli et al, 2014).…”
Section: Targeting the Insect Haemogram And Immune Reactions As A Pesmentioning
confidence: 99%
“…The present results disagreed with the previously reported results since forcefeeding of 3 rd instar larvae of G. mellonella on diet supplemented with 6-BA resulted in significantly prolonged total adult longevity, in a dose-dependent course. However, the current literature contains no information about the prolongation of total adult longevity of insects after treatment with PGRs except a recent study by Çelik and Sak (2021) who investigated the effects of kinetin against A. grisella and recoded significantly prolonged adult longevity of males, at 5 mg/Lkinetin. Interpretation of the shortened total adult longevityof different insects after larval treatments with various PGRs is available (Abdel-Aal, 1996;Broughton et al, 2005;Carbone et al, 2006;Kefford et al, 2008;Chamseddin et al, 2012;Er et al, 2017) while the exact interpretation of prolongation of total adult longevityof G. mellonella after larval feeding on diet mixed with 6-BA, in the present study, is unfortunately available right now.…”
Section: I3 Disturbed Adult Longevity By 6-ba: I31 Total Adult Longevitymentioning
confidence: 99%